2011
DOI: 10.1155/2011/867525
|View full text |Cite
|
Sign up to set email alerts
|

Suspension of Mitotic Activity in Dentate Gyrus of the Hibernating Ground Squirrel

Abstract: Neurogenesis occurs in the adult mammalian hippocampus, a region of the brain important for learning and memory. Hibernation in Siberian ground squirrels provides a natural model to study mitosis as the rapid fall in body temperature in 24 h (from 35-36°C to +4–6°C) permits accumulation of mitotic cells at different stages of the cell cycle. Histological methods used to study adult neurogenesis are limited largely to fixed tissue, and the mitotic state elucidated depends on the specific phase of mitosis at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…Moreover, Hypoxia-inducible factor 1-alpha (HIF-1α) increases after rewarming and remains elevated during euthermy (Ma et al, 2005). Marked synaptogenesis and activation of proliferative stress activated signaling pathways following rewarming from hibernation suggest that AGSs may benefit from restorative processes during periods of inter-bout euthermy (Drew et al, 2004;von der Ohe et al, 2006;Weltzin et al, 2006), and like turtles, restorative processes may contribute to tolerance to ischemia and anoxia (Drew et al, 2011;McGee et al, 2008;Popov et al, 2011). Studies designed to tease out the influence of the hibernation state on protection from hypoxia and I/R in isolated brain tissue found that cold tissue temperature alone could account for enhanced protection in the hibernating state.…”
Section: Resistance To Cerebral Ischemia/reperfusion Injury When Euthmentioning
confidence: 99%
“…Moreover, Hypoxia-inducible factor 1-alpha (HIF-1α) increases after rewarming and remains elevated during euthermy (Ma et al, 2005). Marked synaptogenesis and activation of proliferative stress activated signaling pathways following rewarming from hibernation suggest that AGSs may benefit from restorative processes during periods of inter-bout euthermy (Drew et al, 2004;von der Ohe et al, 2006;Weltzin et al, 2006), and like turtles, restorative processes may contribute to tolerance to ischemia and anoxia (Drew et al, 2011;McGee et al, 2008;Popov et al, 2011). Studies designed to tease out the influence of the hibernation state on protection from hypoxia and I/R in isolated brain tissue found that cold tissue temperature alone could account for enhanced protection in the hibernating state.…”
Section: Resistance To Cerebral Ischemia/reperfusion Injury When Euthmentioning
confidence: 99%
“…We suggested that the high number of dying cells found in the parenchymal regions of hibernating frogs might provide the stimulus for the ventricular zones to proliferate. Instead, Popov et al (2011) demonstrated in the dentate gyrus of the hibernating ground squirrel a decreased mitotic activity, in spite of the presence of a large population of immature cells.…”
Section: Discussionmentioning
confidence: 87%
“…piriform cortex (Barkai and Saar, 2001);and (v) it is the primary pathway by which olfactory information reaches the hippocampus, amygdala, and prefrontal cortex (Shipley et al, 1995). However, this structure has received very little attention in neurobiological studies of aging.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Hypoxia-inducible factor 1-alpha (HIF-1α) increases after rewarming and remains elevated during euthermy (Ma et al, 2005). Marked synaptogenesis and activation of proliferative stress activated signaling pathways following rewarming from hibernation suggest that AGSs may benefit from restorative processes during periods of inter-bout euthermy (Drew et al, 2004;von der Ohe et al, 2006;Weltzin et al, 2006), and like turtles, restorative processes may contribute to tolerance to ischemia and anoxia (Drew et al, 2011;McGee et al, 2008;Popov et al, 2011). Studies designed to tease out the influence of the hibernation state on protection from hypoxia and I/R in isolated brain tissue found that cold tissue temperature alone could account for enhanced protection in the hibernating state.…”
Section: Resistance To Cerebral Ischemia/reperfusion Injury When Euthmentioning
confidence: 99%
See 1 more Smart Citation